2023
DOI: 10.3390/biology12050743
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular Adhesion Molecule 1: More than a Leukocyte Adhesion Molecule

Abstract: Intercellular adhesion molecule 1 (ICAM-1) is a transmembrane protein in the immunoglobulin superfamily expressed on the surface of multiple cell populations and upregulated by inflammatory stimuli. It mediates cellular adhesive interactions by binding to the β2 integrins macrophage antigen 1 and leukocyte function-associated antigen 1, as well as other ligands. It has important roles in the immune system, including in leukocyte adhesion to the endothelium and transendothelial migration, and at the immunologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 267 publications
1
4
0
Order By: Relevance
“…Exploring the connection between JCV status and treatment response might influence the decisions made in therapy [20,21] and certain researchers [22,23] have indicated that detecting the JCV virus in tumor samples has led medical professionals to implement more rigorous treatment plans for affected individuals, than in infected without virus as they opt for less aggressive therapies to mitigate potential treatment-related toxicity and those studies further reinforces the findings from our investigation into identifying the virus. The present study revealed increase levels of ICAM-2 in patients with JCV positivity and this observation implies a possible link between JCV infection and elevated ICAM-2 expression in individuals with prostate cancer [24,48] and the increased levels of ICAM-2 noted in JCV positive prostate cancer patients could have various implications, levels of ICAM-2 have the potential to be used as a diagnostic indicator to identify JCV infection in patients with prostate cancer [25,26]. This discovery could offer insights into the impact of viral infections on prostate cancer and could be relevant for diagnostic or therapeutic purposes and noticeable disparity in ICAM-2 levels, findings from the chi-square test reveal a substantial contrast in ICAM-2 levels among prostate cancer patients who were positive for JCV compared to those who were negative and this implies that the presence of JCV infection had relation with fluctuations in ICAM-2 levels in individuals with prostate cancer [27,28].…”
Section: Discussionsupporting
confidence: 68%
“…Exploring the connection between JCV status and treatment response might influence the decisions made in therapy [20,21] and certain researchers [22,23] have indicated that detecting the JCV virus in tumor samples has led medical professionals to implement more rigorous treatment plans for affected individuals, than in infected without virus as they opt for less aggressive therapies to mitigate potential treatment-related toxicity and those studies further reinforces the findings from our investigation into identifying the virus. The present study revealed increase levels of ICAM-2 in patients with JCV positivity and this observation implies a possible link between JCV infection and elevated ICAM-2 expression in individuals with prostate cancer [24,48] and the increased levels of ICAM-2 noted in JCV positive prostate cancer patients could have various implications, levels of ICAM-2 have the potential to be used as a diagnostic indicator to identify JCV infection in patients with prostate cancer [25,26]. This discovery could offer insights into the impact of viral infections on prostate cancer and could be relevant for diagnostic or therapeutic purposes and noticeable disparity in ICAM-2 levels, findings from the chi-square test reveal a substantial contrast in ICAM-2 levels among prostate cancer patients who were positive for JCV compared to those who were negative and this implies that the presence of JCV infection had relation with fluctuations in ICAM-2 levels in individuals with prostate cancer [27,28].…”
Section: Discussionsupporting
confidence: 68%
“…Transcription of the ICAM-1-coding gene (ICAM-1) is mainly controlled by the proximal gene promoter region, which contains functional binding sites for activator protein 1 (AP-1), specificity protein 1 (SP1), nuclear factor-kappa B (NF-κB), interferon regulatory factors (IRF), ETS1 and signal transducer and activator of transcription (STAT)-1 [83]. Phosphorylation of phosphoinositide-3-kinase (PI3K)-Akt, mitogen-associated protein kinases (MAPKs), jun kinases (JNKs), Janus tyrosine kinases (JAKs) or the cytoskeleton-associated focal adhesion kinase (FAK) and proline-rich tyrosine kinase 2 (Pyk2) are among the major signalling pathways involved in ICAM-1 transcriptional activation [84]. Of particular interest is the PI3K/Akt pathway induced by growth factors such as VEGF, which increases ICAM-1 expression in microvascular endothelial cells through the phosphorylation of eNOS on Ser1177 and nitric oxide (NO) production [85].…”
Section: Icam-1 (Cd54)mentioning
confidence: 99%
“…ICAM-1 (“InterCellular Adhesion Molecule-1”) or CD54 is a cell adhesion molecule of crucial importance during the extravasation of leukocytes at inflammation sites and in the formation and stabilization of immune synapses required for T cell-mediated immune responses [ 53 , 54 , 55 ]. Structurally, ICAM-1 is a type-I transmembrane protein that belongs to the immunoglobulin protein superfamily (IgSF), and comprises five extracellular immunoglobulin domains (D1–D5), one transmembrane domain, and a short cytoplasmic tail that links this molecule with the actin cytoskeleton [ 54 , 56 ].…”
Section: Roles Of Integrin Ligand Icam-1 (Cd54) In the Docking And Up...mentioning
confidence: 99%
“…ICAM-1 (“InterCellular Adhesion Molecule-1”) or CD54 is a cell adhesion molecule of crucial importance during the extravasation of leukocytes at inflammation sites and in the formation and stabilization of immune synapses required for T cell-mediated immune responses [ 53 , 54 , 55 ]. Structurally, ICAM-1 is a type-I transmembrane protein that belongs to the immunoglobulin protein superfamily (IgSF), and comprises five extracellular immunoglobulin domains (D1–D5), one transmembrane domain, and a short cytoplasmic tail that links this molecule with the actin cytoskeleton [ 54 , 56 ]. ICAM-1/CD54 is constitutively expressed at relatively low levels on the endothelium, leukocytes, and many other cell types (including cancer cells), but its expression is dramatically increased by multiple inflammatory stimuli, including TNFα, IFN-γ, and IL-1 (reviewed in [ 57 , 58 , 59 , 60 ]).…”
Section: Roles Of Integrin Ligand Icam-1 (Cd54) In the Docking And Up...mentioning
confidence: 99%